Comparison of perioperative efficacy and indications between laparoscopic capsule-preserving resection and partial nephrectomy for renal angiomyolipoma: a decade-long retrospective study - Haipeng Zhang; Guangcan Yang; Changxiu Tian; Wei Song; Houliang Zhang; Jinliang Ni; Ziming Jiang; Keyi Wang; Bo Peng (World Journal of Surgical Oncology)
Abstract Background This study aims to compare and evaluate the clinical efficacy of laparoscopic capsule-preserving resection (LCPR) and laparoscopic partial nephrectomy (LPN) in the treatment of renal angiomyolipoma (RAML). Multivariate regression analysis was employed to identify patient characteristics that are most suited for LCPR. Methods We retrospectively analyzed the clinical data of 209 patients diagnosed with RAML and treated surgically at our hospital between January 2010 and December 2023. The patients were divided into two groups: 102 in the LCPR group and 109 in the LPN group. Preoperative factors (e.g., age, sex, glomerular filtration rate (GFR), and tumor location), intraoperative factors (e.g., ischemia time and blood loss), and postoperative outcomes (e.g., extubation time, hospitalization duration, and renal function) were recorded. Chi-square tests, independent sample t-tests, and rank-sum tests were applied where appropriate. Logistic regression analysis was used to identify patient characteristics associated with suitability for LCPR. Results No significant differences were observed in the preoperative baseline characteristics (age, sex, or tumor size) between the two groups (P > 0.05). All surgeries in the LCPR group were successfully completed, and no patients required conversion to open surgery. The average operation time was 118.56 ± 44.49 min, the warm ischemia time was 17.40 ± 7.51 min, and the intraoperative blood loss was 197.35 ± 282.64 ml, all of which were significantly lower than in the LPN group (P < 0.05). The incidence of postoperative complications in the LCPR group was 21.6% for Clavien-Dindo grade I and 2.9% for higher-grade complications, significantly lower than the LPN group (33.6% and 8.4%, respectively; P = 0.02). The average postoperative hospital stay in the LCPR group was 6.42 ± 3.01 days, significantly shorter than in the LPN group (9.27 ± 3.24 days; P < 0.001). The average GFR 1-3 days after surgery and the renal function grade 3 months post-surgery were significantly better in the LCPR group compared to the LPN group (P = 0.001). Multivariate regression analysis identified that patients with low preoperative serum creatinine levels, mild clinical symptoms, tumors smaller than 6 cm, and tumors located near the middle of the kidney were more likely to undergo LCPR (P < 0.05). These patients also experienced less renal function deterioration post-surgery. Conclusions Laparoscopic capsule-preserving tumor resection offers significant clinical advantages in treating renal angiomyolipoma. Compared to traditional laparoscopic partial nephrectomy, LCPR results in less intraoperative blood loss, shorter warm ischemia times, lower complication rates, and faster postoperative recovery. Patients with mild clinical symptoms, small tumors, or tumors located in complex regions such as the renal hilum are more suitable for this surgical approach, making it a promising technique for broader clinical application.